The tool of planning agreements - Nicole De Togni (Cidades, Comunidades e Território)
The canonical planning and historiographical perspectives concerning the Italian cities in the second post-war period describe their complex modernization and expansion process mainly due to linear sequences of planning acts and policies. The public housing estates, their models, strategies, and agents are the consolidated interpretative categories to address the Italian boom.The paper aims to question this understanding of the role played by the public powers facing the planning agreements as underexplored tools of Italian planning. Their original interpretation in connection with the post-war Italian planning legislation and the tools of the City and Detailed Plans opens to a nuanced history in the relationship between the public and private sectors, and the practices in the central and expansion areas of the post-war cities.In the Italian legislative context, planning agreements are long-standing arrangements between the public administration and public or private actors, aiming at organizing and disciplining expertise and goods for planning purposes. Mainly interpreted as technical measures to overcome the City Plans constraints in the expansion areas, they rather reflect a stratified experience of punctual negotiation throughout the city, offering a privileged lens to observe tools and practices, professional and administrative networks, demands for social emancipation and renewal of planning processes, at the centre of a complex system of actors, habits, disciplinary and critical positions, leading to a reinterpretation of cultural and professional backgrounds and of social and negotiation processes, which is crucial for a complex reading of the post-war Italian cities.In the second post-war period, the city of Milan offers a significant framework to observe the use and critical understanding of this tool, being at the core of the disciplinary debate and professional expectations of the 1950s and 60s. The meaningful case study of Piazza della Repubblica tower, one of the best-known post-war projects by the architect Giovanni Muzio, is provided.